Multiculturalism-Based Fiqh Learning to Improve Tolerance and Anti-Fanaticism Attitudes in Pesantren - Rusydiyah, Evi Fatimatur; Jazil, Saiful; Zahro, Ahmad (Didaktika Religia, 2023)
This article examines the publication of fiqh learning in pesantren related to increasing tolerance and anti-fanaticism attitudes. Pesantren has emerged as an institution that is able to implement fiqh studies to the fullest.  This research has selected 179 articles to 29 articles based on inclusion and exclusion criteria such as period, document type, and source. PRISMA was used as a guide for article selection in this study. Lens.org, Eric, and Garuda are literature search databases. The results of research through SLR show that fiqh learning methods with innovative approaches can lead to learning achievements for students. The innovative approaches include the method of fiqh multiculturalism can increase the attitude of tolerance and anti-fanaticism, open up to differences, open the horizons of thinking, have analytical acumen, and overcome fanaticism; dialogue method with the result of increasing mutual respect and tolerance; multicultural contextual method with the result of increasing the ability to answer multidimensional problems; integral-holistic method with the result of improving academic, spiritual, emotional, social, and creative aspects; contextual fiqh posmo method with the result of improving understanding of contemporary issues; and multicultural promotion method with the result of improving understanding of multiculturalism and moderate thinking.